SARS-CoV-2 infection in 3,241 School working staffs: Impact of SARS CoV-2 variants of concern [Wild, B.1.1.7 and Omicron]. - Moza Alishaq; Jameela Ali Al Ajmi; Mohammed Shaheen; Mohamed Elgendy; Suni Vinoy; Anil George Thomas; Sam Joseph; Tintu Elizabeth Mathew; Renjith Joseph; Christymol Thomas; Anju K Alex; Bincy Thomas; et al. (PLoS ONE)
Background There is debate over whether physical attendance at school affects the spread of the SARS-CoV-2 pandemic. Methods A cohort of personnel from several schools in Qatar provided nasopharyngeal swabs (NPS) for SARS-CoV-2 RT-PCR and rapid antigen testing. Each of them was monitored for infection until February 2022. Results In total, 3,241 employees gave samples for analysis. Prior to the start of the 2020-2021 academic year (Group I), 3.49% of samples tested positive for SARS-CoV-2. Most of the positive PCR results were from male, senior, non-teaching staff members. Only 110 (3.39%) employees who had enrolled in face-to-face instruction before the B.1.1.7 variant's emergence (Group II), 238 (7.34%) after the B.1.1.7 variant's emergence (Group III), and 410 (12.65%) after the introduction of the Omicron variant (Group IV) had reported infection by PCR test. Most people who tested positive by PCR after enrolling in school were young, female teachers. In the Cox Proportional-Hazards Model, exposure to a confirmed case, the presence of symptoms in the two weeks prior to exposure in all groups-young age in Groups II and III, male gender in Groups I and IV, shared housing in Group III, and the presence of comorbidities in Groups II and III independently predicted SARS-CoV-2 infection in school staff. Conclusion Critical information about the risk of SARS-CoV-2 infection in school workers during the whole pandemic is provided by our study. School operations in Qatar were made safer through initial and ongoing screenings, as well as widespread vaccination of school personnel.